Inside Back Cover: Light‐Controlled Interconversion between a Self‐Assembled Triangle and a Rhombicuboctahedral Sphere (Angew. Chem. Int. Ed. 1/2016). Issue 1 (11th December 2015) - Han, Muxin; Luo, Yuansu; Damaschke, Bernd; Gómez, Laura; Ribas, Xavi; Jose, Anex; Peretzki, Patrick; Seibt, Michael; Clever, Guido H.
Abstract : Stimuli‐responsive structural reorganizations found in nature inspire the synthesis of supramolecular mimics and functional materials. In their Communication onpage 445 ff., G. Clever and co‐workers demonstrate that irradiating small, self‐assembled Pd3 L6 rings based on photochromic ligands with 313 nm light triggers their conversion into rhombicuboctahedral Pd24 L48 spheres measuring 7 nm across. Irradiation at 617 nm fully reverses the process, but with pronouncedly different kinetics.